2008
DOI: 10.1007/s11440-008-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

Computational validation of static and dynamic plate load testing

Abstract: In this paper, the static load plate test and the dynamic load plate test by means of the light falling weight device are assessed utilizing numerical simulations. Simplified computational models of the tested subsoil and of the testing devices are developed, which capture the main effects of both the static and the dynamic load plate test. In extensive parametric studies, the impact of various subsoil conditions on the test results and several sources of error are evaluated and discussed. Computational test r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…According to Van Genuchten method, curve-fitting parameters are estimated based on volumetric water content of soil. Therefore, the best point to estimate and evaluate the curve fitting parameters is the middle point between residuals and saturated water content, [33], [34].…”
Section: Methodsmentioning
confidence: 99%
“…According to Van Genuchten method, curve-fitting parameters are estimated based on volumetric water content of soil. Therefore, the best point to estimate and evaluate the curve fitting parameters is the middle point between residuals and saturated water content, [33], [34].…”
Section: Methodsmentioning
confidence: 99%
“…Hildebrand (2003) in turn even suggested that LFWD should not be used on granular base courses. Later analyses of theoretical mathematical models and experiences of other researchers have even questioned the sense of looking for close relationships between the two testing methods, pointing out that the differences between them are too great (Adam et al 2009, Krawczyk and Mackiewicz 2016, Węgliński 2018). Among other things, the static test differs from the dynamic test in terms of the maximum extent of the loading effect.…”
Section: Discussionmentioning
confidence: 99%
“…3). The deformation modulus E def,2 from the second loading stage in the load-displacement diagram was calculated with the following equation [23]:…”
Section: Methodsmentioning
confidence: 99%